2009
DOI: 10.1038/eye.2009.193
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous closure of retinal pigment epithelium microrip in the natural course of central serous chorioretinopathy

Abstract: Purpose To study the natural course of changes observed in the retinal pigment epithelium (RPE) on spectral domain OCT transverse and RPE fit C-scans corresponding to the leakage point observed on fundus fluorescein angiograms in central serous chorioretinopathy (CSC). Methods Thirteen patients with acute CSC were prospectively enrolled and followed up for 6 months. All were examined using Zeiss Cirrus HD-OCT Model 4000. Transverse and RPE fit C-scans corresponding to point of leakage were superimposed on an O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
(19 reference statements)
1
16
0
3
Order By: Relevance
“…In contrast to a typical large RPE rip characterized by a torn RPE and a bared choroid, an RPE microrip is a small defect in the RPE layer, which may close spontaneously. 31 The present study in association with the investigations mentioned above showed that OCT characteristics of CSC were an increased subfoveal choroidal thickness with dilated hyporeflective lumina (vessels) beneath a thinned inner choroidal layer in the ICGA hyperfluorescent area, RPE detachments with hyporeflectivity beneath the detached RPE, and RPE microrips. These features may be useful to differentiate CSC from masquerading diseases affecting the macular region, such as Vogt-Koyanagi-Harada's syndrome, uveal effusion syndrome, polypoidal choroidal vasculopathy, posterior scleritis, pregnancy-induced choroidopathy, choroidal hemangioma, lymphoblastic leukemia, or other metastatic choroidal disease.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast to a typical large RPE rip characterized by a torn RPE and a bared choroid, an RPE microrip is a small defect in the RPE layer, which may close spontaneously. 31 The present study in association with the investigations mentioned above showed that OCT characteristics of CSC were an increased subfoveal choroidal thickness with dilated hyporeflective lumina (vessels) beneath a thinned inner choroidal layer in the ICGA hyperfluorescent area, RPE detachments with hyporeflectivity beneath the detached RPE, and RPE microrips. These features may be useful to differentiate CSC from masquerading diseases affecting the macular region, such as Vogt-Koyanagi-Harada's syndrome, uveal effusion syndrome, polypoidal choroidal vasculopathy, posterior scleritis, pregnancy-induced choroidopathy, choroidal hemangioma, lymphoblastic leukemia, or other metastatic choroidal disease.…”
Section: Discussionsupporting
confidence: 84%
“…This finding does not mean that the change of choroidal vasculature follows the absorption of SRF. It remains unclear at first; the natural resolution of SRF results from either decreased effusion from choroid or healing of the RPE microrip, or possibly both, as suggested by the report by Gupta et al 22 Nevertheless, considering the fact that the SFCT after resolution decreased from the baseline regardless of treatment, the decrement of choroidal thickness might be an essential prerequisite or concomitant phenomenon for healing of CSC.…”
Section: Discussionmentioning
confidence: 96%
“…In a prospective study, Gupta et al 32 have reported that within the course of time, cases with acute CSC may experience resolution of subretinal fluid with a closure of microrip; and RPE hypertrophy may occur at the site of leakage. In a prospective study, Gupta et al 32 have reported that within the course of time, cases with acute CSC may experience resolution of subretinal fluid with a closure of microrip; and RPE hypertrophy may occur at the site of leakage.…”
Section: Discussionmentioning
confidence: 99%